Psychological Morbidity across the CKD Trajectory: A Multi-Center Comparative Study of Pre-Dialysis versus Maintenance Dialysis Patients in Bangladesh (Journal of Comilla Medical College Teachers' Association, 2026)
Background: Chronic Kidney Disease (CKD) imposes a significant psychological burden on patients, which may evolve as the disease progresses from the pre-dialysis stage to requiring maintenance dialysis. Understanding this shift is crucial for delivering holistic care in resource-limited settings, such as Bangladesh.Objective: This study aimed to compare the levels of depression, anxiety, and stress between pre-dialysis and post-dialysis CKD patients.Methods:  A comparative cohort study was conducted from July 2024 to June 2025 at Eastern Medical College & Hospital (EMCH) and another tertiary care hospital. A total of 80 participants were recruited, comprising 40 in the pre-dialysis (CKD stage 4 and 5) group and 40 in the post-dialysis (on maintenance hemodialysis for more than 3 months) group. The Depression, Anxiety, and Stress Scale (DASS-21) were used for psychological assessment. Data were analyzed using SPSS version 23.0, employing independent t-tests and Chi-square tests.Results: The post-dialysis group demonstrated significantly higher mean scores for depression (18.4 vs. 11.2, p